The efficacy of a pseudo-ceramide and eucalyptus extract containing lotion on dry scalp skin - Takagi Y; Ning X; Takahashi A; Ishizaki C; Nishizaka T; Kaizu K; Miyaki M; Yamamuro H; Kawashima M (Dove Medical Press, 2018)
Yutaka Takagi,1 Xuanhe Ning,1 Akihiko Takahashi,1 Chiaki Ishizaki,2 Takahiro Nishizaka,1 Kazuhiro Kaizu,1 Masahiro Miyaki,1 Hotaka Yamamuro,1 Makoto Kawashima3 1Skin Care Product Research, Kao Corporation, Tokyo, Japan; 2Ebisu Skin Research Center, Inforward, Inc., Tokyo, Japan; 3Department of Dermatology, Tokyo Women’s Medical University, Tokyo, Japan Objective: Dry and scaly conditions on the scalp are often observed in patients with atopic dermatitis, seborrheic dermatitis and/or pityriasis capitis. Those scalp lesions often exhibit low barrier function and reduced ceramide levels. Therefore, a clinical study was conducted to evaluate the efficacy of topical application of a pseudo-ceramide and eucalyptus extract-containing lotion on the scalps of patients with skin diseases.Methods: Thirty-four subjects participated in this study (atopic dermatitis: 19 subjects; seborrheic dermatitis: 6 subjects; pityriasis capitis: 9 subjects). After 4 weeks of daily treatment with a pseudo-ceramide and eucalyptus extract-containing lotion, the skin symptoms had significantly improved in all patients with those skin diseases.Results: Skin dryness, scaling, and erythema were significantly improved by treatment with the lotion. The moisture-retention ability of the scalp was significantly increased and itchiness, evaluated using a visual analog scale, decreased significantly. Accompanying those improvements was a significant improvement in the quality of life of the subjects, evaluated by the Skindex-16®.Conclusion: From these results, we conclude that this pseudo-ceramide and eucalyptus extract-containing lotion effectively improved the dry and scaly conditions of the scalp as well as the quality of life of subjects with atopic dermatitis, seborrheic dermatitis, or pityriasis capitis. Keywords: formulation, skin care, moisturization, scalp lotion, sensitive skin, inflammation